Correction to: Stereo reconstruction from microscopic images for computer-assisted ophthalmic surgery(International Journal of Computer Assisted Radiology and Surgery, 10.1007/s11548-024-03177-0) - Peter, Rebekka; Moreira, Sofia; Tagliabue, Eleonora; Hillenbrand, Matthias; Nunes, Rita G.; Mathis-Ullrich, Franziska (International Journal of Computer Assisted Radiology and Surgery, 2024)
In the original version of this article, figures 2 and 3 are displayed 4 times bigger than intended. The figures, including text in the figures, are unnecessarily large and disturb the overall layout. The Figures 2 and 3 should have appeared as shown below. (Figure presented.) (Figure presented.) Experimental setup for vertical distance dv estimation between instrument and lens Overview of acquired data. a–f POR, g–i PHA, j–l SYN The layout of the two tables is overall highly inconsistent. While for Table 1 the numbers are right-bound, for Table 2 the numbers are left-bound. For table 3 it is mixed. The alignment of the columns w. r. t. to the headlines is not clear and seems inconsistent as well. The added line between row 4/5 is not centered (closer to row 5 than to row 4). The column width is not equally distributed which leads to a unclear and unorganized overall appearance. The Tables 1, 2 and 3 should have appeared as shown below. (Table presented.) (Table presented.) (Table presented.) Results of stereo reconstruction without and with cornea. All values are in μm Experiment Data Our approach Baseline: SGMa MAE SD MAE SD 1b: Open-sky scenario PHA (w/o cornea) 118 64 611 985 SYN (w/o cornea) 51 67 66 164 No rect. of corneal distort. SYN (w/ cornea) 305 339 478 180 2a: Rect. of corneal distort. SYN (w/ cornea) 73 54 205 1171 aAll points with an Euclidean distance >2000μm are not considered Results of instrument to lens distance sensing experiment (1b) on a PHA and POR eye without cornea. All values are in μm Δ1 AE(Δ1) Δ2 AE(Δ2) Δ3 AE(Δ3) MAE MAE(Pos. 1-3) Pos. 1 674 174 463 37 467 33 80 PHA Pos. 2 680 180 702 202 796 296 226 145 Pos. 3 528 28 679 179 324 176 128 Pos. 1 343 157 853 353 206 294 268 POR Pos. 2 257 243 669 169 732 232 215 194 Pos. 3 471 29 335 165 398 102 99 Influence of a change in the geometrical and optical parameters of the ray tracing scene 10% increase of Rac kac Rpc kpc dc dach nc Ref No rect. of corneal distort. MAE 73 77 78 82 80 64 90 60 305 SD 110 115 113 116 115 108 117 53 339 MAE and SD of the stereo reconstruction of SYN data when the radius and conical constants of the anterior and posterior corneal surfaces Rac, kac, Rpc, and kpc, the corneal thickness dc, the anterior chamber depth dach and the refractive index of the cornea nc are varied by 10% individually. All values are in μm The original article has been corrected.
CRIS-Team Scopus Importer:2024-12-06